Platelet count and clinical outcomes in hospitalized patients with COVID-19 pneumonia - Siniscalchi, Carmine; Di Micco, Pierpaolo; Guerra, Angela; Simoni, Riccardo; Magro, Julia; Parise, Alberto; Cerundolo, Nicoletta; Imbalzano, Egidio; Tana, Claudio; Finardi, Lorenzo; Meschi, Tiziana (Frontiers in Medicine, 2025)
BackgroundThrombocytopenia has been associated with poor outcomes in various infectious diseases, including COVID-19. This study investigates the relationship between platelet (PLT) count at hospital admission and clinical characteristics, treatments, and outcomes in patients with COVID-19 pneumonia.MethodsWe retrospectively analyzed 797 patients hospitalized for COVID-19 pneumonia, stratifying them into three groups by platelet count: <150,000/mm3 (22%), 150,000–400,000/mm3 (76%), and >400,000/mm3 (2.5%).ResultsPatients with PLT < 150,000/mm3, more frequently male, and had a higher prevalence of cirrhosis and fibrosis. They presented less severe respiratory impairment and lower inflammatory markers. They also showed lower use of enoxaparin and a higher use of fondaparinux. Mortality was at the limits of significance in this group (37% vs. 28 and 20%, p = 0.056), and thrombocytopenia was independently associated with increased risk of in-hospital death (HR 1.483, 95% CI 1.023–2.150; p = 0.037).ConclusionThrombocytopenia on admission independently predicts mortality in patients hospitalized with COVID-19 pneumonia.